Nexus of Access to Electricity and Financial Development in Namibia: Application of Fourier Cointegration and Frequency Domain Causality - Mosikari, Teboho Jeremiah (International Journal of Energy Economics and Policy, 2026)
This work investigates the relationship between access to electricity and financial development in Namibia. Three different forms of electricity access have been used in the analysis and the data is collected from World Development Indicators (WDI) for the span 1992 to 2022. The paper used the Fourie cointegration and frequency domain causality analysis to determine cointegration and direction of the causality at different frequencies. Based on three equations measuring access to electricity by different receipts it was determined that there is cointegration among access to electricity and financial development. Overall results shown a positive connection among financial development and access to electricity. Long-run findings indicate that there is causality moving from access to electricity for total population will lead to financial development. These findings suggest that as more people in Namibia have access to electricity this will lead to financial development. Policy implication suggested is that financial sectors must develop a reasonable and enabling energy loans (capitals) via tax holidays on sustainable energy connections for urban and rural areas.